China & ANU - Sima, William (ANU Press, 2016)
The Pacific War and its aftermath radically transformed Australian perceptions of what was then called the 'Near North'. Many recognised that in the postwar world Australia's strategic interests and economic fortunes called for a new understanding of Asia and the Pacific. China loomed large in these calculations. Based on extensive research and featuring rare archival documents and photographs, China & ANU introduces the diplomats, adventurers and scholars who contributed to Australia's engagement with China, the 'Chinese Commonwealth' and our region from the 1940s-1950s. In particular, this book focusses on the interconnection between Australia's first diplomat-scholars in China and the founding of Chinese Studies at the newly established Australian National University.